Public service rules : revised to 1st January, 2000 - Federal Republic of Nigeria (Lagos : Federal Government Press, 2000)
This is a revised version of the Public Service rules and regulations guiding civil servants in Nigeria (revised to Jan. 1, 2000).
oif 25/02/15; nmn 29/03/19
Arch.
Keywords: Civil service; Civil service ethics; Public service rules; Nigeria